ENVIRONMENTAL DAMAGE AND GLOBAL WARMING ARE LABOR LAW ISSUES: A REFLECTION - Widiastiani, Nindry Sulistya (Domus Legalis Cogitatio, 2024)
This article aims to reflect on whether labor law relates to handling environmental damage and global warming issues, also becoming an alternative tool to solve those issues. The main reason for the reflection is that labor law and environmental law have the same actor, entrepreneurs as employers, with their companies. This article is written with a conceptual approach to employers and their companies' activities in both labor and environmental law concepts. The reflection shows that labor law has a strategic position in economic activities, which could be a way to solve environmental damage and global warming issues because of employers and their companies' production process. Labor law could solve the issues: First, laws about environmental protection and occupational health and security management systems should be integrated. Second, the authorization of the Company Regulation and Compulsory Company Manpower Report mechanism should be used to control whether employers obey and fulfil environmental protection laws. Third, the Workers' Union/Laborers' Union's voice and movement in environmental protection relating to companies as workplaces should be utilized. Fourth, support work-from-home and digital workplace trends as an alternative choice that is environmentally friendly because it decreases traffic for workers who use their personal vehicles to go to and back from their workplaces.